GENDER CHARACTERISTICS OF THE BACKGROUND OF THE ELECTRICAL ACTIVITY OF THE BRAIN DURING VISUAL DYSFUNCTION - Redka, I.V. (World of Medicine and Biology, 2013)
The aim of this study was to determine the gender-specifics of the EEG spectral characteristics of children 8 to 12 years of age with visual dysfunction. 31 children with congenital visual dysfunction and 49 sighted psychoneurologic healthy children were participated in the study. Gender characteristics of EEG spectral characteristics depend on the state of visual function. The absolute spectral intensity of beta-2 band was significantly higher in the sighted girls compared to the sighted boys. This is how the emotional sphere of individuals of different sexes. The absolute spectral power of the delta band was significantly higher in boys with congenital visual dysfunction compared to girls with congenital visual dysfunction. This indicates a greater sensitivity of males to unfavorable factors (limiting the visual afferent).